Produção e rentabilidade da cultura do tomateiro afetadas pela fertilização e pelo sistema de condução - Fontes , Paulo Cezar; Nazar , Ricardo Antonio; Pelúzio de Campos , Joênes (Revista Ceres, 2025)
The aim of this experiment was to evaluate tomato yield and profit as affected by fertilization levels (1.1 and 2.2 t/ha of 4-14-8) and tomato production method («traditional» and «tutorado»).